2014
DOI: 10.1007/s11033-013-2984-6
|View full text |Cite
|
Sign up to set email alerts
|

Glycine betaine protects tomato (Solanum lycopersicum) plants at low temperature by inducing fatty acid desaturase7 and lipoxygenase gene expression

Abstract: Cold stress is among the environmental stressors limiting productivity, yield and quality of agricultural plants. Tolerance to cold stress is associated with the increased unsaturated fatty acids ratio in the plant membranes which are also known to be substrates of octadecanoid pathway for jasmonate and other oxylipins biosynthesis. Accumulation of osmoprotectant, glycine betaine (GB) is well known to be effective in the protecting membranes and mitigating cold stress effects but, the mode of action is poorly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 47 publications
2
33
0
1
Order By: Relevance
“…; Miura & Furumoto ; Karabudak et al . ). Three abiotic factors, drought, salinity and low temperature, known to induce water deficiency in plants trigger similar downstream signal transduction pathways involved in protection against cellular dehydration.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Miura & Furumoto ; Karabudak et al . ). Three abiotic factors, drought, salinity and low temperature, known to induce water deficiency in plants trigger similar downstream signal transduction pathways involved in protection against cellular dehydration.…”
Section: Discussionmentioning
confidence: 97%
“…; Karabudak et al . ) and is a prerequisite for the biosynthesis of jasmonic acid ( JA ; Schaller & Stintzi ), which is a positive regulator of ICE 1 (Zhao et al . ; Hu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Soluble sugars also could enhance plant growth similar to hormones21. Some amino acids such as proline were osmoprotectants, which had great importance in improved stress tolerance of plant622. The growth rate of plant is closely related to N supply23.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous application of GB in soybean (Glycine max L.) enhanced salt tolerance supporting enzymes involved in protecting mechanism [36]. The role of GB in cold stress responses and indicated that GB role in inducing FAD7 and LOX expressions for providing protection against cold stress in tomato plants which could lead to desaturation of lipid peroxidation products by increasing membrane stability and genes involved in stress defense mechanism via octadecanoid pathway [37].…”
Section: Discussionmentioning
confidence: 99%